Local Governance and Community Development Initiatives : Contributions for Community Development Programs in Timor-Leste - Butterworth, David (World Bank, Washington, DC, 2017)
What happens when the state's vision and expanding reach bring it into contact with traditional value systems and governance structures? In what circumstances can the distribution of resources in a fragile society prevent-or exacerbate-conflict within and between communities? How do state expansion and public spending impact upon societal expectations of the state and state legitimacy? This report examines these questions through the lens of access, claiming, and decision making in government-sponsored community development programs. The findings illustrate the hurdles faced by government and development actors operating in pluralistic societies, and provide input on how local governance and decision making might be incorporated to enrich programming. This report aims to provide the government of Timor-Leste, particularly those responsible for decentralization, community development, and local governance planning, with information to inform their determination of an appropriate mix of models for local development. The relative priority the government will ultimately give to these different models, partly a trade-off between speed and depth, will impact on the way in which development and local governance are understood and taken on board by rural communities. This report finds that the achievement of the dual goals of state legitimacy and sustainable, effective local development hinges in large part on the willingness of state officials (and the donors that support them) to engage productively with communities and locally legitimate customary systems of authority.